Voronezh State Medical University named after N. N. Burdenko - A. A. Zuikova; D. Yu. Bugrimov; O. N. Krasnorutskaya; Yu. A. Kotova (Лечащий Врач)
Lung damage caused by the SARS-CoV-2 virus and the depletion of the immune system is a serious obstacle to recovery patients with COVID-19-associated pneumonia. Stimulating regeneration factors can help repair damaged lung tissue. Prognostically significant indicators of the effectiveness of restorative treatment of patients after the acute stage of COVID-19-associated pneumonia should be based on the criteria for lung tissue regeneration and restoration of the immune system. Patients with COVID-19 should be examined to select a rehabilitation treatment program, taking into account individual indications and to assess the safety of the planned measures. The experience of the practical use of an immunomodulator with a reparative effect of sodium deoxyribonucleate in programs for the rehabilitation treatment of patients with communityacquired pneumonia with confirmed or suspected COVID-19, DN0 or DN1 with CT-1-2 or CT-2-3 (mild, moderate and moderate course), undergoing the stage of rehabilitation treatment in the conditions outpatient medical organizations. The presented rehabilitation treatment programs, tested in outpatient medical institutions, can be fully applied in the conditions of sanatorium-resort rehabilitation of phthisiopulmonary sanatoriums, which will significantly increase the overall quality of medical care not only at the stages of treatment, but also at rehabilitation.